2010
DOI: 10.1159/000322327
|View full text |Cite
|
Sign up to set email alerts
|

Non-Selective Cation Channel-Mediated Ca<sup>2+</sup>-Entry and Activation of Ca<sup>2+</sup>/Calmodulin-Dependent Kinase II Contribute to G<sub>2</sub>/M Cell Cycle Arrest and Survival of Irradiated Leukemia Cells

Abstract: Genotoxic stress induces cell cycle arrest and DNA repair which may enable tumor cells to survive radiation therapy. Here, we defined the role of Ca2+ signaling in the cell cycle control and survival of chronic myeloid leukemia (CML) cells subjected to ionizing radiation (IR). To this end, K562 erythroid leukemia cells were irradiated (0-10 Gy). Tumor survival was analyzed by clonogenic survival assay and cell cycle progression via flow cytometry. Plasma membrane cation conductance was assessed by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 57 publications
(64 reference statements)
2
50
0
Order By: Relevance
“…The present study demonstrates IR-induced Ca 2þ signaling and activation of Ca IR-induced modifications of Ca 2þ signaling and/or K þ channel activity have been reported by our group in different tumor entities such as lung adenocarcinoma (28), leukemia cells (27,29), or glioblastoma (21). In lung adenocarcinoma, K þ channels contribute to an elevated glucose uptake by the irradiated cells.…”
Section: Discussionsupporting
confidence: 79%
“…The present study demonstrates IR-induced Ca 2þ signaling and activation of Ca IR-induced modifications of Ca 2þ signaling and/or K þ channel activity have been reported by our group in different tumor entities such as lung adenocarcinoma (28), leukemia cells (27,29), or glioblastoma (21). In lung adenocarcinoma, K þ channels contribute to an elevated glucose uptake by the irradiated cells.…”
Section: Discussionsupporting
confidence: 79%
“…CaMKII, in turn, has been reported to regulate the cell cycle via inactivation of cdc25 isoforms and subsequent inactivation of cdc2 (CDK1) [39-42]. To define putative Ca 2+ -mediated VPA effects on cell cycle, VPA (0 or 750 µM for 48 h)-treated U251 cells were probed against cdc25A, -B, -C and cdc2 as well as against the phosphorylated forms of these proteins by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their role in maintaining the calcium homeostasis (de Groot et al, 2011), some reports have also suggested TRPV5 and TRPV6 as important biomarkers in tumor development and progression (Heise et al, 2010). This has been proved in prostate, breast, thyroid, colon, pancreatic and ovary cancers.…”
Section: Discussionmentioning
confidence: 98%